Marriage by design a novel (New York Ballantine Books, 2006)
The top designer at her father's bridal design company, Mia Savard faces a milestone in her life, after turning thirty and suddenly finding herself single again after being dumped, a situation that is complicated when her most recent design is leaked to the competition and P.I. Joe Kerr is called in to find the insider responsible.
"An Ivy Books mass market original".
Keywords: Business intelligence -- Fiction; Fashion designers -- Fiction; Love stories